Using Norway spruce clones in Swedish forestry: implications of clones for management. Issue 5 (4th July 2019) - Rosvall, Ola; Bradshaw, Richard H. W.; Egertsdotter, Ulrika; Ingvarsson, Pär K.; Mullin, Tim J.; Wu, Harry
ABSTRACT: This final paper of the series discusses implications of various aspects of using clones in forestry. Benefits from using clones are considerable. A large benefit arises from the ability to deploy genetic gain much sooner than is possible through conventional seed orchards. This benefit applies even to the use of clones to implement family forestry, even though the clones themselves are not tested. The requirement for genetic diversity at both the stand and landscape levels requires active management to ensure that diversity is conserved. This is achieved partly through the management of breeding populations, as well as by managing the genetic diversity and number of genotypes deployed in clone mixtures. A numerical example is given comparing diversity of clone and seed orchard deployment over time. Many aspects of managing concerns about using clones are about communication to clarify public perceptions and establishing a code of practice.